Evaluation of chemical composition, antioxidant activity, and gut microbiota associated with pumpkin juice fermented by Rhodobacter sphaeroides. (1st February 2023) - Wang, Yaqin; Fan, Lingjia; Huang, Jintao; Liang, Jingjing; Wang, Xingnan; Ren, Yichen; Li, Hongcai; Yue, Tianli; Gao, Zhenpeng
Highlights: Fermentation of fruit and vegetable juice with Rhodobacter sphaeroides. R. sphaeroides fermented pumpkin juice to produce a new substance for coenzyme Q10. R. sphaeroides fermented pumpkin juice to increased antioxidant activity. R. sphaeroides fermented pumpkin juice to improve gut microbiota structure of mice. Abstract: To prepare pumpkin juice (PJ) rich in coenzyme Q10, this study analyzed the chemical composition, antioxidant activity, and gut microbiota of pumpkin juice fermented by Rhodobacter sphaeroides (RPJ). The number of viable bacteria in the juice reached 2.8 × 10 8 CFU/mL; the fermentation process mainly consumed glucose and sucrose; the total sugar content was reduced, β -carotene was reduced, and a new antioxidant substance, coenzyme Q10, appeared at a content of 12.345 mg/L; levels of volatile alcohols, esters, and ketones significantly increased; and antioxidation ability improved, particularly the ferric ion reducing antioxidant power activity. The gut microbiota of mice shifted by increasing Lactobacillus and Bifidobacterium and protected the gut barrier by reducing Proteobacteria after 48 h of fermentation. Pumpkin juice fermented by Rhodobacter sphaeroides not only produces bioactive substances with antioxidant capacity but can also regulate the gut microbiota of mice.